2017
DOI: 10.1038/srep42676
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for a role of the adrenergic nervous system in generalized anxiety disorder

Abstract: Generalized anxiety disorder (GAD) is a common chronic condition that is understudied compared to other psychiatric disorders. An altered adrenergic function has been reported in GAD, however direct evidence for genetic susceptibility is missing. This study evaluated the associations of gene variants in adrenergic receptors (ADRs) with GAD, with the involvement of stressful events. Data were obtained from 844 French community-dwelling elderly aged 65 or over. Anxiety disorders were assessed using the Mini-Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Given the implication of cortical neurons in addiction, anxiety, and pain disorders, compounds with mechanisms of action related to these pathologies were examined prior to HCP analysis. MOR agonists and antagonists were chosen for their dual role in both pain and addiction, and compounds targeting alpha adrenergic receptors (ADR-A) were cho-sen for their role in depression and anxiety disorders [29] , [34][35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the implication of cortical neurons in addiction, anxiety, and pain disorders, compounds with mechanisms of action related to these pathologies were examined prior to HCP analysis. MOR agonists and antagonists were chosen for their dual role in both pain and addiction, and compounds targeting alpha adrenergic receptors (ADR-A) were cho-sen for their role in depression and anxiety disorders [29] , [34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the in vivo responses to MOR agonism, since studies have shown inhibition of prefrontal cortical neuronal activity after heroin infusions along with synaptic loss after morphine administration in animal studies [ 36 , 37 ]. Furthermore, ADR-A agonists cause analgesia and sedation through reductions in norepinephrine release, which is associated with reduced neuronal excitability [34][35] , [38] . These data suggest that the cortical spheroids respond reliably and predictably to compounds targeting receptor subtypes relevant to neurological disorders impacting cortical circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Further, researchers observed elevated serum catecholamine concentrations in patients with GAD, indicating the excess of NE ( Homan et al, 2015 ; Reader et al, 2015 ). Preliminary evidence suggests that single-nucleotide polymorphism involved in the function of adrenergic receptors is a susceptibility factor for general anxiety disorder ( Zhang et al, 2017 ). Animal model studies found that antagonism of β-adrenergic receptors within central nerve system could attenuate the anxiogenic effects of cocaine ( Wenzel et al, 2014 ) and disrupted anxiety-like phenotypes including aversive, fear and stress-related behaviors ( Kindt et al, 2014 ; McCall et al, 2017 ).…”
Section: The Role Of Ne In Mdd and Adsmentioning
confidence: 99%
“…For example, treatment with prazosin, an α 1 -AR inverse agonist, was successful in improving nightmare symptoms in patients with PTSD (posttraumatic stress disorder) [9]. Moreover, adrenergic receptors variants (including ADRA1A) were recently identified as the susceptibility factor for GAD (generalized anxiety disorders) [10].…”
Section: Introductionmentioning
confidence: 99%